If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8x+3(1-8x)=-4x+31
We simplify the equation to the form, which is simple to understand
-8x+3(1-8x)=-4x+31
Reorder the terms in parentheses
-8x+(+3-24x)=-4x+31
Remove unnecessary parentheses
-8x+3-24x=-4x+31
We move all terms containing x to the left and all other terms to the right.
-8x-24x+4x=+31-3
We simplify left and right side of the equation.
-28x=+28
We divide both sides of the equation by -28 to get x.
x=-1
| 0.25(12+4x)-0.5(8+2x)= | | x^3*x^6*x^9= | | 5=-3b-4-3 | | 3x^3+16x^2+15x-18=0 | | 11=n/6-5 | | 2x-8=-3x+2 | | 1-3p-1=-18 | | 11-7x=107-28x | | 21=43-2r | | 2(x+3)=x-13 | | 52=5d+7 | | w-22= | | a/12-3=2 | | 2(x+3)+4x=6+6x | | 69-2x=16x+19 | | 1.3(x-13)=14 | | 9x+20y=85 | | 6x^3+7x^2-3x= | | -10x=2x^2 | | .5n+5n=7n-18 | | -5x+8x-33=21 | | (x-9)-(-5+3)=1 | | 0.6(x-13)=14 | | 6x^2+7x^2-3x= | | 10+(-11)+(-12)= | | 3(44)+2r=240 | | 10+b/18=11 | | 2w+2(3w+1)=50 | | 45x+100= | | -85+5x+3x=43 | | 6(x-a)=4(x-5) | | 2[6x-7(x-1)]=5x-21 |